Analysis of the Implementation of Micro Teaching in Developing the Pedagogical Competence of Prospective Student Teachers in Higher Education - Pipin Danu Marti; Nur Azizah; Riski Apriansyah; Siti Afifatun (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
Micro teaching serves as a strategic learning approach in teacher education programs to strengthen the pedagogical competence of prospective teachers through structured teaching practice, reflection, and feedback. This study aims to analyze the implementation of micro teaching in developing the pedagogical competence of prospective student teachers in higher education. The research employed a qualitative case study design involving lecturer supervisors and prospective student teachers participating in a micro teaching course. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using data condensation, data display, and conclusion drawing with triangulation to ensure data credibility. The findings indicate that the implementation of micro teaching contributes significantly to the development of pedagogical competence by improving lesson planning, instructional delivery, classroom management, learning media utilization, communication skills, and reflective teaching practices. Furthermore, continuous feedback from lecturers and peers encourages self-evaluation and professional growth among prospective teachers. Despite challenges such as limited teaching time, performance anxiety, and varying levels of teaching readiness, the program effectively prepares students for authentic classroom experiences. The study concludes that systematic and reflective micro teaching is an essential component of teacher education programs, fostering pedagogical competence and enhancing the professional readiness of prospective teachers in higher education.